Predictors of early dropout in outpatient buprenorphine/naloxone treatment - Marcovitz, David E. (Am J Addict, 2016)
BACKGROUND AND OBJECTIVES: Identifying predictors of early drop out from outpatient treatment of opioid use disorder (OUD) with buprenorphine/naloxone (BN) may improve care for subgroups requiring more intensive engagement to achieve stabilization. However, previous research on predictors of dropout among this population has yielded mixed results. The aim of the present study was to elucidate these mixed findings by simultaneously evaluating a range of putative risk factors that may predict dropout in BN maintenance treatment. METHODS: Outpatient medical records and weekly supervised urine toxicology results were retrospectively reviewed for patients at two community psychiatric clinics (n=202): a private hospital clinic (n=84) and a federally qualified health center (n=118). A forward stepwise logistic regression was utilized to investigate the association between early dropout (i.e., discontinuing treatment or buprenorphine non-adherence within the first three months of clinic entry) and extracted sociodemographic, clinical, substance use, and treatment history variables. RESULTS: Overall, 56 of 202 participants (27.7%) dropped out of treatment. The multivariable analysis indicated that age under 25 (B=1.47, SEB=.52, p <.01) and opioid use in month 1 (B=1.50, SEB=.41, p<.001) were significantly associated with early dropout; those with a history of suicide attempt were significantly less likely to drop out (B=−1.44, SEB = .67, p<.05). CONCLUSIONS AND SCIENTIFIC SIGNIFICANCE: Consistent with previous research, younger age and use of opioids during the first month of treatment predicted early dropout. Having a history of prior suicide attempt was associated with 3-month BN treatment retention, which has not been previously reported.